Między doświadczeniem a wydarzeniem. O zobowiązaniach świadka - Ciarkowska, Anna (Zagadnienia Rodzajów Literackich, 2019)
The aim of this article is to outline the definition of literary testimony and to define the position of the witness as an obliged writer. A basic definition reveals testimonial literature as a set of texts, ontologically uncertain, full of tensions and aporias. These tensions between testimony and document, testimony and autobiography, and also relations truth-fiction, individual-collective, experience-event delimit the area of literary testimony. In this complicated structer the witness, charged, limited by the obligation with is double. This is the obligation to take an action — bear witness and the obligation towards the Other.